PROBLEMS OF COMPILATION OF TEXTBOOKS AT THE PRESENT STAGE - Авлакулова Озода Наримановна (Journals Park Publishing, 2024)
Modern education requires constant development and updating of educational materials. However, compiling high-quality textbooks has become a difficult task at the present stage. In this article, we will look at the main problems faced by authors and publishers, as well as possible ways to solve them.
Keywords: manual, textbook, education, material, method.